Fault Seal Analysis using Heat Flow Data - RAZA, MUHAMMAD AHMED (2013)
The problem of fault seal analysis is very critical in evaluation of petroleum play and has been studied for many years. Various approaches have been defined in literature. Among them are the juxtaposition analysis of stratigraphy along the fault and evaluation of fault zone material through the usage of lithological algorithms. However these methods have provided results which need calibration according to the area. In this work, a method has been presented for the analysis of fault seals. This method uses the heat flow data along the formations to evaluate the sealing behavior of the fault. The variance of heat flow data across the fault plane records the sealing and non sealing behavior signatures.